2012
DOI: 10.1590/s1516-35982012000500024
|View full text |Cite
|
Sign up to set email alerts
|

Características físico-químicas e sensoriais da carne de cordeiros terminados com dietas contendo cana-de-açúcar ou silagem de milho e dois níveis de concentrado

Abstract: 15 kg de peso corporal. Os animais foram confinados em baias individuais e abatidos aos 32 kg. As dietas e os músculos estudados não influenciaram o pH aos 45 minutos (6,56) e 24 horas (5,62) após o abate nem a capacidade de retenção de água (58,38%) e a perda de peso por cocção (34,04%). A cor da carne e da gordura subcutânea não diferiu entre as dietas, entretanto a cor da carne variou entre os músculos longissimus lumborum e triceps brachii. A força de cisalhamento (1,85 kgf/cm 2 ) não foi afetada pelas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
5
9
0
4
Order By: Relevance
“…Skatol is considered as the main responsible for the rejection of sheep meat (Ferrão et al, 2009). Analyzing the replacement of corn silage with sugarcane, Leão et al (2012) found a higher skatol content in the meat of animals fed silage (0.79 µg g -1 fat) compared to those fed sugarcane (0.38 µg g -1 fat).…”
Section: Resultsmentioning
confidence: 99%
“…Skatol is considered as the main responsible for the rejection of sheep meat (Ferrão et al, 2009). Analyzing the replacement of corn silage with sugarcane, Leão et al (2012) found a higher skatol content in the meat of animals fed silage (0.79 µg g -1 fat) compared to those fed sugarcane (0.38 µg g -1 fat).…”
Section: Resultsmentioning
confidence: 99%
“…No se encontró efecto de los tratamientos sobre la CRA, presentando promedios de 47,5%. En este sentido, Leão et al (2012), al evaluar las características físico-químicas y sensoriales de carne de cordero terminados con ensilaje de sorgo y concentrado, reportaron 58,38%; Sañudo (1991) manifestó que el sistema de producción y la alimentación no afecta la CRA en ovinos; sin embargo, Ramírez et al (2007) valorando la calidad de la carne y el análisis sensorial en ovinos de pelo y lana provenientes de engorda intensiva en México, encontraron efecto significativo (p≤<0,05), con valores medios de 42,4 y 32,2%, respectivamente, similares a los encontrados.…”
Section: Resultados Y Discusiónunclassified
“…Because it is a trait indicative of the meat quality, it is important to emphasize the detection of normal values of pH decline, as it can affect other characteristics such as color, tenderness, and cooking weight loss (Leão et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For meat color analysis, irrespective of the SFT with which the lambs were slaughtered, the color of the meat of the lambs from this experiment can be considered light, as their L* was between 33.40 and 37.60, since lightness values for sheep are considered to vary from 30.03 to 49.47 (Warris et al, 2003;Leão et al, 2012). Teixeira et al (2005) and Martinez-Cerezo et al (2005) found values between 11.01 and 23.04 for a* and 4.2 and 9.07 for b*.…”
Section: Discussionmentioning
confidence: 99%